2007
DOI: 10.1002/app.26551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vibration extrusion on high‐density polyethylene

Abstract: A new type of extrusion apparatus with a hydraulic vibration field was self-developed to study the effects of vibration on the rheological behavior, mechanical properties, and morphology of high-density polyethylene (HDPE) during the process of extrusion. In the research, the morphology and mechanical properties of specimens produced by conventional extrusion molding were used for comparison with specimens obtained via vibration extrusion molding. The research showed that the extrusion property of the HDPE mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Obviously, the axial molecular orientation in PP pipes is unfavorable to their application. So far, many processing technologies have been proposed to erase axial molecular orientation and improve hoop strength such as solid extrusion, vibration extrusion, and rotation extrusion …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the axial molecular orientation in PP pipes is unfavorable to their application. So far, many processing technologies have been proposed to erase axial molecular orientation and improve hoop strength such as solid extrusion, vibration extrusion, and rotation extrusion …”
Section: Introductionmentioning
confidence: 99%
“…8 Obviously, the axial molecular orientation in PP pipes is unfavorable to their application. So far, many processing technologies have been proposed to erase axial molecular orientation and improve hoop strength such as solid extrusion, 9 vibration extrusion, 10 and rotation extrusion. 11 During rotation extrusion, with the superposition of axial flow and drag hoop flow caused by mandrel or die rotation, polymer melts move forward helically.…”
Section: Introductionmentioning
confidence: 99%
“…It is also one of the most crucial approaches to improve the properties of the polymer materials. In recent years, the vibration technique has been applied to polymer extrusion processing and gained a lot of detailed investigations 1–11. The vibration force field introduced into polymer extrusion processing affects the molecular movement and the rheological behavior of the polymer melt, which in turn affects the morphological development of the final extruded products and then the final properties.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al10 successfully used a mandrel‐rotating die to obtain high‐hoop‐strength HDPE pipe by self‐reinforcement. Gao et al11 developed a new type of extrusion apparatus with a hydraulic vibration field to produce HDPE sheets, and found that both the longitudinal and transverse yield strengths of the HDPE specimens increased.…”
Section: Introductionmentioning
confidence: 99%
“…Also several researchers studied the densification for granular material packing and extrusion of polyethylene under vibration, but the characteristics of the materials processed in these cases are different from those encountered in biomass densification (Kim and Pyun 1995;Lesaffrea et al 2000;Gao et al 2007). Therefore, results of the cited studies cannot be used with confidence to predict whether or not vibration-assisted compaction can be successfully employed when dealing with biomass.…”
Section: Introductionmentioning
confidence: 99%